The Commodity Application System Assessment Method (CSAM) on Post harvest Handling of Citrus Keprok (Citrus reticulate) from the Dis - Sri Mulyani; Bambang Admadi; I Gede Nyoman Arya Suyasa (APTA and DTIP FTP UGM, 2017)
This study aims to identify the causes of impact and damage of post-harvest handling of citrusfrom Pupuan District to Denpasar District and determine how to implement the best handlingsystems. The study group consists of farmers in the Pupuan District, Tabanan. Samples weretaken by purposive sampling method with 62 farmers from three villages. Data was collectedthrough questionnaires from participants handling tangerines from farmers, wholesalers,transporters and retailers. Factors causing damaged tangerines were identified at the farm levelin the process of sorting and packing at the level of the wholesaler in the process of dismantlingand sorting and a higher level with retailers handling stock for display. The impact of post-harvest losses at farm level is 10%, wholesalers and suppliers 11% and retailers18%.